PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Ranisa Devi; Hafiziani Eka Putri; Tiara Yogiarni (STKIP Subang, 2025)
The limited ability of elementary school students to solve mathematical problems that require problem-solving skills has become a crucial issue in addressing the challenges of 21st-century education. This study aims to investigate the effect of the Problem Based Learning (PBL) model on students’ mathematical problem-solving abilities at the elementary level. A quantitative approach was used with a quasi-experimental design of the nonequivalent control group type. The research sample consisted of two classes, VA and VC, from a public elementary school in Purwakarta Regency during the 2024/2025 academic year, with 25 students in each class. Class VA served as the experimental group and received instruction using the PBL model, while class VC, as the control group, was taught using the Student Teams Achievement Divisions (STAD) cooperative learning model. Data were collected through essay tests developed based on Polya’s problem-solving stages, administered during both pretest and posttest. The analysis results showed a significant effect of the Problem Based Learning (PBL) model on enhancing the mathematical problemsolving abilities of elementary school students.